EFFECT OF HARVESTING MICROALGAE (CHLORELLA SP.) CONTINUOUSLY TO ITS GROWTH IN THE FOTOBIOREAKTOR - Ma'rufatin, Anies (Jurnal Rekayasa Lingkungan, 2016)
Currently, the photobioreactor (FBR) has been developed and utilized to investigate (knowing in detail) the metabolic processes of cells of microorganisms, such as microalgae. FBR technology MTAP (Multi Tubular Photobioreactor Airlift) is a continuous system that is closed and controled for the growth. Then, this technology conducted continuous harvesting trial. Continuous harvesting system is cultivated by reducing of microalgae solution volume then is added by new solution of FBR MTAP system in operation. The number of reactors in the FBR MTAP are two reactors were used that Reactor 1 and Reactor 2. Microalgae was grown in 21 DAP (Days After Planting) and then harvested by reducing the volume 16.7% in each reactor in DAP 12. Based on the results of cells density, harvesting in the first phase, the optimum growth occurred at DAP 7 for Reactor 1 and Reactor 2, while harvesting their optimum growth phase II DAP 16 for Reactor 1 and DAP 19 for Reactor 2. Comparison of cell density on both reactors FBR MTAP conducted trial period of harvesting microalgae Chlorella sp. freshwater DAP 12 and DAP 21 are optimal to be done continuously without dewatering and sterilization performed the FBR system MTAP.Key words: photobioreactor, continuous harvesting, microalgae growth, cell density, Chlorella sp.